Implementasi Persona Physica (Kanonik Perseorangan) lewat Sakramen Baptis bagi Kehidupan Umat Beriman Dewasa Ini - Sianturi, Vincentius Andre; Subiantoro, Teddy (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2024)
This article was prepared to analyze the implementation of persona physica in the sacrament of baptism for the development of the faith life of Catholics today. This analysis was of course inspired by concern over the large number of believers who do not yet understand fundamentally what persona physics is and its benefits for everyday life. First of all, persona physica displays a person's ability (persona) to obtain their rights and obligations in the eyes of the law (ecclesiastical law). This ability can only be obtained through valid initiation practices in the tradition of the Catholic Church. In this case, the sacrament of baptism is an important element for a person to obtain persona physica (individual canonical position). Such rights and obligations empower a person to achieve the fullness of God's salvation in the life of faith and society (social) in which he lives.